2019
DOI: 10.1111/all.13849
|View full text |Cite
|
Sign up to set email alerts
|

miR‐10a‐5p is increased in atopic dermatitis and has capacity to inhibit keratinocyte proliferation

Abstract: Background: miR-10a-5p has been shown to regulate cancer cell proliferation and invasiveness and endothelial cell inflammatory responses. The function of miR-10a-5p in the skin has not been previously studied. The aim of the current study was to examine miR-10a-5p expression, regulation, and function in keratinocytes (KCs) in association with atopic dermatitis (AD). Methods:The expression of miR-10a-5p and its target genes was analyzed using RT-qPCR, mRNA array analysis, in situ hybridization, and immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Additionally, miR-10a was found to inhibit cell proliferation by targeting BCL6 in diffuse large B-cell lymphoma [47]. MiR-10a-5p was proved to have the capacity to inhibit keratinocyte proliferation [48]. According to these reports, miR-148a and miR-10a can inhibit cell proliferation which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, miR-10a was found to inhibit cell proliferation by targeting BCL6 in diffuse large B-cell lymphoma [47]. MiR-10a-5p was proved to have the capacity to inhibit keratinocyte proliferation [48]. According to these reports, miR-148a and miR-10a can inhibit cell proliferation which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Egr-miR-10a-5p was predicted to target the NECTIN2, COLGALT1, COL5A2 , and DDTL genes, which were involved in the positive regulation of natural killer cell–mediated cytotoxicity and T-cell receptor signaling pathway, collagen fibril organization, collagen catabolic process, tumor necrosis factor production, and ERK1 and ERK2 cascades, respectively (Stanietsky et al, 2013 ; Park et al, 2017 ; Miyatake et al, 2018 ). It has been reported that hsa-miR-10a-5p had a role in regulating the proliferation and invasiveness of cancer cells and inflammatory responses in endothelial cells (Vaher et al, 2019 ). miR-10a-5p inhibited MAP3K7 and β-transducin repeat-containing gene expression, thereby reducing NF-κB activation and displaying anti-inflammatory effects in the athero-susceptible endothelium (Fang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing was conducted to analyze the ncRNAs (miRNAs, circRNAs, and lncRNAs) profiles in the two types of ELVs, and bioinformatics analysis of the 20 most abundant miRNAs in the two types of ELVs was performed to explore the possible biological processes and pathways associated with pathogenicity and the host immune response. These ELVs contain small RNA species, including specific miRNAs that are homologous to host miRNAs with known immunomodulatory roles (Zhang et al, 2016 ; Vaher et al, 2019 ). The results demonstrated that the most abundant miRNAs in both types of ELVs might be new candidates for the mechanism of parasite–parasite communication and parasite–host interactions of ELVs in parasitic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CCL5 was identified as a novel, direct target of miR-146a [ 31 ]. It is worth mentioning that the upregulation of miR-10a-5p, miR-29b, miR-223 and miR-151a have also been described in the inflammatory response and keratinocyte apoptosis for AD patients [ 75 , 76 , 77 , 78 ] ( Table 1 ).…”
Section: Role Of Mirnas In the Skin Pathogenesis Of Cutaneous Immumentioning
confidence: 99%